Production of bioplastic from agricultural waste - Nur Nazirah, Zulkafli (2014)
Plastic has been a vital part of our life. However, disposal of these non-degradable petroleum-derived plastic has threaten our ecosystem. Hence, extensive research has been conducted to find the best substitute to solve this problem. Much interest has been gained in developing biodegradable plastic. Among other potential biodegradable plastic, polyhydroxybutyrate (PHB) has gained much attention and developed for industrial scale production. PHB are accumulated during fermentation process and act as energy source in microbial cells. However, the major problem in commercializing PHB is its high production cost due to its expensive carbon source and tedious procedures of using pure cultures. Thus, utilization of other cheap and renewable culture has been explored. In this study, agricultural waste has been chosen as the potential carbon source for fermentation using Bacillus subtilis to produce PHB. The high glucose content in the sugarcane and pineapple waste juice has making it as the potential substrates. A laboratory study was conducted to screen the effect of five potential factors; temperature, pH, agitation speed, substrate to nutrient ratio and types of waste, towards the production. A total of 16 experiments have been conducted in 48 hours of cultivation time using aerobic condition in shake flask. This study had shown that temperature and agitation speed had given the most significant effect toward PHB synthesis. Temperature is known to give a significant on fermentation since different bacteria requires different temperature for optimum production. Agitation speed should be controlled since too much speed could affect the shear force hence break the bacterial cell. Interaction between factors also has been analysed and interaction between factor of temperature and agitation speed and interaction between temperature and types of waste has shown the highest contribution towards production PHB